THE PERCEPTUAL TERRITORY MODEL IN THE WATER HOUSES ON STILTS FOUND IN THE HERITAGE AREA ON THE KUIN RIVERBANK IN BANJARMASIN - Kusnadi, Giosia Pele Widjaja, Regi (Jurnal Riset Arsitektur, 2017)
Abstract - The limited amount of land available on the mainland of the Kuin region has triggered the emergence of permanent stilt houses on the river resulting in new settlements as part of the Kuin region. As a matter of fact, these houses on stilts on the riverbank in the Kuin Kampong do not have a well-defined division marker with the air-based space of the river, so that this particular territory is only based on the perception of the individual owners. This research study aims to shed light on territorial behavior and the perceptual territory model to be found at this location. The data collection method was initially conducted by way of direct observation and conducting interviews with various prominent society figures selected from the local community. After the case study object had been selected, in-depth research was conducted into territorial behavior observed in these case studies. The result indicates that there are two perceptual territory models out of the six cases examined based on their territorial attitude. The first one concerns the perceptual territory model pointing toward the front (mainland) up to the road network, and pointing backwards, to the river. On the other hand, on the immediate left and right side of the buildings, they press close on the space owned by their neighbors. The second one comprises the perceptual territory model pointing toward the mainland (reaching the houses across) pointing backwards to the the river, and to the immediate left or right of the buildings. Keywords: Territory, Perceptual Theory, Territoriality, Culture of Settlement